1995
DOI: 10.2307/3579006
|View full text |Cite
|
Sign up to set email alerts
|

Liver Toxicity Induced by Combined External-Beam Irradiation and Radioimmunoglobulin Therapy

Abstract: High-dose radiation therapy for liver metastases of gastrointestinal malignancies might be improved by combining external-beam irradiation and radioimmunoglobulin therapy. We studied the liver toxicity of the proposed combination in healthy beagle dogs. A total dose of 30 Gy to the whole liver, delivered in 2-Gy fractions over 3 weeks, resulted in mild, temporary veno-occlusive disease (VOD) in three of three dogs. Reversible bone marrow damage was noted after two intravenous injections of 18.5 MBq of yttrium-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…The threshold dose for wholeliver irradiation without chemotherapy is supposed to be 20 -30 Gy (21,22). In patients who undergo combined radiation therapy and chemotherapy or combined radiation therapy and immunotherapy, the risk for development of radiation-induced liver disease is higher (23,24). Findings in studies in animals have suggested that liver irradiation at a dose higher than the threshold dose is followed by progressive liver fibrosis and cirrhosis (25).…”
mentioning
confidence: 98%
“…The threshold dose for wholeliver irradiation without chemotherapy is supposed to be 20 -30 Gy (21,22). In patients who undergo combined radiation therapy and chemotherapy or combined radiation therapy and immunotherapy, the risk for development of radiation-induced liver disease is higher (23,24). Findings in studies in animals have suggested that liver irradiation at a dose higher than the threshold dose is followed by progressive liver fibrosis and cirrhosis (25).…”
mentioning
confidence: 98%
“…On the other hand, the liver is a highly radiosensitive organ: the development of radiation-induced liver disease (RILD) is considered to be a major dose limiting complication in abdominal irradiation [8]. The threshold dose for whole liver irradiation is assumed to be between 20 and 30 Gy [9].…”
Section: Introductionmentioning
confidence: 99%
“…An experimental study of combined RT and RIT has been performed in beagle dogs. In the combined therapy group, two of three dogs had to be sacrificed because of liver radiation necrosis and 30% weight loss 4. The liver toxicity might have been partially due to the use of 90 Y‐labeled MAbs that resulted in a nonspecific accumulation in the liver.…”
Section: Introductionmentioning
confidence: 99%